Optimised exergy efficiency of a combined flash spray desalinator recovering discharge thermal energy. Issue 40 (26th August 2016) - Hosseini Araghi, A.; Khiadani, M.; Hooman, K.; Lucas, G.
Abstract: This study focuses on an individualised exergy analysis approach for optimising the exergy efficiencies of the high irreversible components for a new discharge thermal energy combined desalination (DTECD) system. DTECD is a newly introduced energy recovery system to use the latent heat of waste steam. It is a combination of closed and open thermodynamic cycles, which cogenerates power and pure water. Based on the extra steam in an ammonia plant, two scenarios were modelled with respect to the exergy performance, which were individualised to find the irreversibility of each component. The results showed that exergy efficiency of the entire system is about 50%. Also, it was found that the working fluid evaporator and vacuum flash desalinator were the most exergy destructive equipment in the closed power cycle and open water cycle, respectively. The performance of the DTECD system utilising a vacuum single-stage spray flash evaporator is compared with similar technologies. Finally, recommendations are provided as to how the exergy efficiencies of these low-efficiency pieces of equipment can be optimised by changing the operating parameters such as vacuum pressure and working fluid concentration.